Reconstruction of the Geometric Décor Technology of the Bronze Age Ceramics in Siberia - Eva Lamina (EXARC Journal, 2017)
The grassland and forest steppes ranging from the Ural to the Altai-Sayan mountains were dominated by Andronovo Family cultures during the second millennium BC (the Bronze Age) (Koryakova and Epimakhov 2007; Мартынов 2005). The Andronovo dated ceramic series were characterized by a distinctly expressed geometric ornamentation style.